Kelengkapan Imunisasi Dasar pada Masa Pandemi Covid-19: Narrative Review - Kusvitasari, Hairiana; Yuliantie, Putri (Utan Kayu Publishing, 2022)
The COVID-19 pandemic has disrupted health systems around the world and impacted immunization service systems. There was a decrease in immunization coverage during the COVID-19 pandemic, marked by incomplete basic immunizations for infants and toddlers. The purpose of this research is to review evidence of the completeness of basic immunization during the COVID-19 pandemic. The method used in this study is a narrative review by reviewing 7 relevant articles from 2020-2022 and accessed from PubMed, Science Direct, Willey, EBSCO, and 1 Gray literature Google Scholar databases. The results of the review found 3 major themes, namely, the impact of COVID-19 on the completeness of basic immunization, the factors that affect the completeness of basic immunization, and the government's efforts to improve the completeness of basic immunization during the COVID-19 pandemic. Abstrak: Pandemi COVID-19 telah mengganggu sistem kesehatan di seluruh dunia dan berdampak pada sistem pelayanan imunisasi. Terjadi penurunan cakupan imunisasi selama masa pandemi COVID-19 berlangsung, ditandai dengan ketidaklengkapan imunisasi dasar pada bayi dan balita. Tujuan penelitian ini adalah untuk mereview evidence dari kelengkapan imunisasi dasar pada masa pandemi COVID-19. Metode yang digunakan dalam penelitian ini adalah narrative review dengan melakukan review 7 artikel yang relevan dari tahun 2020-2022 dan diakses pada data base PubMed, Science Direct, Willey, EBSCO dan 1 Gray literature Google Scholar. Hasil review ditemukan 3 tema besar yaitu, dampak COVID-19 terhadap kelengkapan imunisasi dasar, faktor-faktor yang mempengaruhi kelengakapn imunisasi dasar dan upaya pemerintah dalam meningkatkan kelengkapan imunisasi dasar pada masa pandemic COVID-19.